Radiation Recall Masquerading as an Infectious Process - Santhosshi Narayanan; Bilal Mujtaba; Bilal Mujtaba; Mohamed Elshikh; Mohamed Elshikh; Gauri R Varadhachary (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2017)
Cellulitis and other infections are common in cancer patients, especially patients who are immunosuppressed following chemotherapy. When patients do not respond to antimicrobial therapy as expected, it is imperative for clinicians to consider other treatment-related conditions in the differential diagnosis. One such condition unique to cancer patients who have received radiation therapy is radiation recall, which may masquerade as an infectious phenomenon and can be a recurrent issue in a previously irradiated area.We report a case of radiation recall cellulitis and myositis during treatment with  gemcitabine, cisplatin, and nab-paclitaxel after radiation therapy. Upfront identification of radiation recall facilitates its timely diagnosis and management.